STUDENT’S ATTITUDES TOWARD HOMOSEXUALITY - Fatbardha Osmanaga (European Scientific Journal, ESJ, 2015)
People’s attitudes toward homosexuality, especially student’s attitudes, have constituted the focus of many studies conducted around the world. The paper aims to measure the attitudes towards the homosexuality of the students of Psychology and Social Work branches, studying for a Bachelor degree in the Faculty of Educational Sciences, Department of Psychology and Social Work, University "Luigj Gurakuqi", Shkodër, Albania. In addition, the paper aims to analyze the impact of students’ study programme on their attitudes toward homosexuality, the impact of students’ academic course, the impact of students’ residence, and the impact of students’ age on their attitudes towards homosexuality. This study however, made use of a questionnaire. The measuring instrument used in the study was “Attitudes Towards Sexual Orientation: An Adaption of Herek’s ATLG Survey” (the adaption is made by Benjamin J. Stefonik). The data collected from the questionnaire was analyzed by means of the SPSS program, variant 20. 249 students of the Psychology and Social Work branches of Bachelor degree, University "Luigj Gurakuqi", Shkodër, Albania, participated in the study. Also, 128 students (51,4% of students participating in the study) were students of the Psychology branch, while 121 students (48,6%) were students of the Social Work branch. The paper concluded that there is an existence of prejudice attitudes towards homosexuality. The students of Psychology branch have more positive attitudes towards homosexuality than the students of Social Work branch. Nevertheless, this relationship is not statistically significant. It is very important that there should be a gross improvement on student’s attitudes towards homosexuality. This is especially for the students of Social Work branch, the students of the second and third academic courses, and for students who live in the city. Consequently, the major strategies for improving student’s attitudes towards homosexuality were recommended.